Architectural value for urban tourism placemaking to rejuvenate the cityscape in Johor Bahru - Abdul Rahman, Noraslinda; Halim, Norhazliza; Zakariya, Khalilah (Institute of Physics Publishing, 2018)
This study aims to investigate the social significance of urban placemaking in shaping the architectural values of the cityscapes for sustainable tourism. The Johor Bahru City Centre was developed with explicit intention to have public open spaces that can encourage tourism activities in the urban area. Cultural and natural resources are essential to make the tourism industry grow successfully. Historical and archaeological sites also become a part of tourist attraction such as museums, state landmarks, parks, sculptures, monuments and others. In this respect, the architectural values of the city are the tangible assets that the city has, while the cultural and natural values are the intangible assets that can be captured from places that shape tourist perception. Placemaking supports the concept of generating places that improve the relationship between users and space, by increasing the sense of place. This is where the values of architecture must be preserved in order to maintain the identity of the region. Based on an extensive review of the literature and empirical works, this research examines Johor Bahru by extracting its similarities and differences with cities in Singapore and Australia, to derive at a better understanding of the significance of the architectural value and urban tourism placemaking in rejuvenating the city values attached to physical spaces. The benchmarking study analyses the values of architecture and discusses the advantages resulting from various architectural characters in tourism. These relationships are essential to understanding the role of architectural value for urban tourism placemaking in rejuvenating the city. This study found that there is a complex nature of the generations of architectural elements through placemaking.